Classification of banks based on the financial recovery index using discriminant analysis by applying it to a sample of banks registered on the Amman Stock Exchange for the period (2000-2021) - Yousef, Rawaa Ahmad (Journal of Economic, Administrative and Legal Sciences, 2024)
The research aims to build a cognitive framework for the subject of financial recovery, as the ability to classify banks into financially recovering banks and others that are not financially recovering will help the financial authorities in taking a set of supportive measures for banks that are not financially recovering in terms of increasing their capital adequacy or reducing the granting of bad loans. As well as providing financial advice to her to improve her financial situation. This research relies on the use of discriminant analysis to classify the Jordanian banks listed on the Amman Stock Exchange as a research sample for the period (2000-2021) according to the financial recovery index into financially recovering banks and others that are not financially recovering and using a set of financial indicators (rate of return/total assets, and owned capital). / Loans, owned capital / deposits) to measure financial recovery and prove its hypotheses. The research sample included (12) banks listed on the Amman Stock Exchange. The research concluded with a set of conclusions and recommendations. One of the most important conclusions is that the discriminant coefficients for the variables were as follows: capital/loans (0.867), rate of return/assets (0.482), capital/deposits (-0.380) and that the standard discriminant function will be D = -0.380 Log(X1) + 0.482 Log(X2) + 0.867 X3 it is also divided into two groups: the first is financially recovering, which includes (the Housing Bank for Trade and Finance, the Arab Jordan Investment Bank, the Investment Bank, the Money Bank of Jordan, Cairo Amman Bank, the Bank of Jordan, the Jordan National Bank, and the Arab Bank), and the second is: not financially recovering, which includes (the Bank of Jordan). Kuwait, Jordan Commercial Bank, Union Bank, Arab Banking Corporation Bank / Jordan). From the results it is clear that the variable (capital / loans) comes first in distinguishing between the two groups, followed by the variable (rate of return / assets), followed by the variable (capital / deposits).
Keywords: financial recovery; discriminatory analysis